(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
One of the defining characteristics of literature is its ability to generate multiple meanings and interpretations. While the orality of Ezenwa Ohaeto’s poetry and performance have received more positive criticisms by critics as well as acceptance, his use of metaphor as a potent amour in poetry seems to have been neglected, hence, it has received less attention by critics. This paper is set to investigate Ohaeto’s use of metaphor in his poetry using Conceptual Metaphor Theory. This work attempts a textual and sub-textual analysis of conventional language into special effects by the poet which often leads to the poetic effectiveness and literary style of the poet. Motivated by the scanty scholarly linguistic studies on metaphors in his poetry, this paper examines the different categories and functions of metaphors in his poems. Building on qualitative research methodology, Ohaeto’s select poems from his collection, Bullets for Buntings as primary data are studied and analysed with a view to examining his reliance on metaphors as discursive strategies to question socio-political issues in Nigerian and by extension, Africa. Again, this paper identified and addressed some aspects of metaphors in Ohaeto’s poems using contextual model in bringing out his aesthetic contributions to scholarship. It also demonstrated that metaphors play contextual roles such as being interactional cognitive tool in the hands of the poet. It is found out that the poet deployed metaphors as linguistic armories to question and address socio-political and cultural problems in order to bring about radical changes in his milieu. Metaphor to a very large extent is found to be one of the versifier’s favourite devices in writing.